Layout solutions for organizational and technological structures promising car-repair depot with flexible asynchronous streams of cars repair - Myamlin, V. V. (Science and Transport Progress, 2010)
The disadvantages of traditional fixed production lines for repair of wagons are pointed out. The advantages of flexible asynchronous wagon-repair stream are shown. Various configuration decisions of the organization-andtechnological structures allowing the realization of these streams are presented. Some special terms of wagon-repair production are refined.